Development and Functional Analysis of Lithocarpus polystachyus (wall.) Rehd Black Tea - Yuqian Liu; Teng Teng; Kun Ye; Guolan Zhou; Xiulong Yang; De-Gang Zhao; Yichen Zhao (Applied Sciences, 2022)
This study examined the development conditions and functional properties of a novel compound tea Lithocarpus polystachyus (wall.) Rehd (L. polystachyus, LPR) black tea (LPRBT). The compound tea was developed by fermentation using fresh leaves (Camellia sinensis cv. Qianmei 601) as the main raw material with LPR powder as an additive. Based on the single factor and orthogonal tests with sensory scores as indicators, a withered leaves–LPR powder mass ratio of 9:1 with a 6 h fermentation time was determined to be the production condition of LPRBT with a sensory score of 89.09. In addition, phlorizin content, anti-oxidation function, hypoglycemic function, and tumor suppressor effect of LPRBT were measured. The results demonstrated that LPRBT phlorizin content was significantly higher than apple. It also showed that the equivalent 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) radical clearance rate with Vitamin C (Vc) and the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical clearance rate was 81% of Vc. Both hydroxyl and superoxide anion radical clearance increased with the increase in LPRBT amount. LPRBT also showed a good inhibitory effect on α-glucosidase and α-amylase, indicating certain hypoglycemic activity. Moreover, it inhibited the growth of HeLa and A549 cancer cells showing tumor suppressor activity. This study provides a reference for the development and application of LPR food products.